Pengaruh Variasi Berat Saccharomyces cereviceae dan Waktu Fermentasi Kulit Nangka Terhadap Kadar Bioetanol yang Dihasilkan - rizqi Karina Utami; Sri Puji Ganefati; Sarjito Eko Windarso (Poltekkes Kemenkes Yogyakarta, 2015)
To suffice the demand of energy consumption, alternative fuels is needed to be developed, suchas bioethanol. Bioethanol is chemical solution which is produced from various plants, fruits, or any part of plant which contain starch, glucose and cellulose. Jackfruit rind has 14,752 % glucose, where from the preliminary test, with Saccharomyces cereviceae addition, the fruit waste could be fermented for producing bioethanol. The purpose of this study was to know the effect of various weights of Saccharomyces cereviceae (i.e. 0%, 25%, 50% dan 75%) and variation fermentation durations (i.e. 4,5 days, 7,5 days, and 10,5 days) of jackfruit rind toward the concentration of the yielded bioethanol by conducting a post test with control group designed experiment. The maximum concentration of bioethanol obtained was 5,63731 % which was produced by using 50% of Saccharomyces cereviceae and from 7,5 days fermentation. The statistical analysis test using one way anova test at 95% level of confidence, concludes that the differences among the ethanol concentrations produced by those various Saccharomyces cereviceae weight and fermentation time are significant.